Disolución conyugal y su incidencia en el trastorno de ansiedad por separación en un niño de 5 años de dad de la ciudad de Babahoyo - Franco Guerra, Angie Michelle (2021)
This case study details a 5 year old boy living in the city of Babahoyo who after experiencing a marital dissolution of his parents, how that situation affects him to present symptoms of Separation Anxiety Disorder. It was identified that the patient presented a significant anxiety symptomatology and how these symptoms negatively affect his life process. With the knowledge acquired, it was possible to work on the different components that trigger such as the behavioral, affective, cognitive and somatic areas. For the collection of important data, several psychometric tests were applied, such as the HTP test and the Spence Child Anxiety Scale (SCAS), as a support to verify the frequency and intensity of the symptoms of the disorder. Therefore, an approach focused on psychoeducation and how to manage the process of marital dissolution for the child was carried out.